Abstracts - Kathryn Atchison, DDS, MPH (Blackwell Synergy, 2002)
In 1999, HRSA commissioned an evaluation of the impact of general dentistry (AEGD and GPR) training programs on treatment of underserved patients and provision of advanced services. Methods: The evaluation included a stratified random survey of dental school graduates of 1989, 1993, and 1997, and asked about participation in postgraduate training, types of patient populations served, community service activities, and types of services provided. Data reduction using factor analysis was performed on types of patients served, services provided, and sources of payment for the three nonspecialty groups to assess differences between general dentists with advanced training and those with none